2012
DOI: 10.3354/meps09539
|View full text |Cite
|
Sign up to set email alerts
|

Linking climate variability, productivity and stress to demography in a long-lived seabird

Abstract: We examined the reproductive ecology of black-legged kittiwakes Rissa tridactyla in several breeding colonies in the North Pacific to test if inter-annual changes in the Pacific Decadal Oscillation (PDO), Winter Ice Cover (ICI), or local sea-surface temperature (SST) predict changes in productivity (fledglings per nest) or nutritional stress (corticosterone). We explored the implications of the observed variation in productivity and stress for projected population dynamics based on a previously demonstrated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 52 publications
2
63
0
Order By: Relevance
“…There is accumulating evidence for changes in biological communities associated with ecosystem shifts in the Bering Sea (Grebmeier et al, 2006), and it has been suggested that the prolonged regimes observed during the last decades may be detrimental to populations of seabirds and northern fur seals (Callorhinus ursinus) breeding at the Pribilof Islands (Stabeno et al, 2012). Piscivorous birds on the Pribilofs have been shown to experience greater food limitation during cold years (Kitaysky, Unpubl data;Benowitz-Fredericks et al, 2008; this study; Satterthwaite et al, 2012), and a recent analysis of the relationship between environmental variables, productivity and CORT levels of seabirds suggests a potential decline of both Pribilof colonies if current cold conditions persist in the North Pacific (Satterthwaite et al, 2012). Although there were relatively cold conditions for the Bering Sea in 2009 (Stabeno et al, 2012) and murres breeding on both Pribilof Islands were more foodlimited (higher CORT and lower co-attendance compared to Bogoslof), St. Paul birds were able to attain a similar level of energy balance as birds on St. George.…”
Section: Foraging Behaviormentioning
confidence: 77%
See 1 more Smart Citation
“…There is accumulating evidence for changes in biological communities associated with ecosystem shifts in the Bering Sea (Grebmeier et al, 2006), and it has been suggested that the prolonged regimes observed during the last decades may be detrimental to populations of seabirds and northern fur seals (Callorhinus ursinus) breeding at the Pribilof Islands (Stabeno et al, 2012). Piscivorous birds on the Pribilofs have been shown to experience greater food limitation during cold years (Kitaysky, Unpubl data;Benowitz-Fredericks et al, 2008; this study; Satterthwaite et al, 2012), and a recent analysis of the relationship between environmental variables, productivity and CORT levels of seabirds suggests a potential decline of both Pribilof colonies if current cold conditions persist in the North Pacific (Satterthwaite et al, 2012). Although there were relatively cold conditions for the Bering Sea in 2009 (Stabeno et al, 2012) and murres breeding on both Pribilof Islands were more foodlimited (higher CORT and lower co-attendance compared to Bogoslof), St. Paul birds were able to attain a similar level of energy balance as birds on St. George.…”
Section: Foraging Behaviormentioning
confidence: 77%
“…Such regimes have been shown to affect the abundance and quality of forage fish and invertebrates (Litzow et al, 2006). Annual variation in oceanographic conditions around the Pribilofs has been shown to influence seabirds breeding on the islands, with higher levels of nutritional stress of piscivorous seabirds during cold years attributed to poor foraging conditions on the continental shelf (Benowitz-Fredericks et al, 2008;Satterthwaite et al, 2012). Key forage fish species, such as the juvenile walleye pollock (Sinclair et al, 2008), are less abundant on the continental shelf during cold years because they either disperse or travel deeper to avoid cold waters (Hollowed et al, 2012).…”
mentioning
confidence: 99%
“…In seabirds, increased CORT secretion is associated with low food availability (Doody et al, 2008;Kitaysky et al, 2007;Kitaysky et al, 2010;Dorresteijn et al, 2012) and in many species plasma CORT correlates inversely with population parameters such as reproductive success, survival and population trends (Buck et al, 2007;Kitaysky et al, 2007;Kitaysky et al, 2010;Harding et al, 2011;Dorresteijn et al, 2012;Satterthwaite et al, 2012). Chicks experience food limitation when their parents are unable or unwilling to compensate for food shortages (Harding et al, 2009;Fairhurst et al, 2012a;Jacobs et al, 2013), thus presenting a direct physiological response of individuals to changes in their nutritional environment.…”
Section: Introductionmentioning
confidence: 99%
“…In normal flow years (2007,2009) There is a demonstrated link between prey availability and reproductive output in seabirds (Hall and Kress 2004;Votier et al 2009;Satterthwaite et al 2012). Fledging success is affected both directly and indirectly by poor foraging conditions; food availability can directly affect adult and chick survival, and low prey availability can lead to longer distance adult foraging trips, longer foraging trip duration, lower adult nest attendance, and, ultimately, higher nest abandonment rates (Anderson et al 2005).…”
Section: Discussionmentioning
confidence: 99%